Improve the efficiency of Battery Cooling System in E Vehicle by Nano-fluids with CFD Analysis. Issue 1 (March 2021) - Vinoth Kumar, H; Saravanakumar, S; Sivakumar, A; Gokul, M; Jagadheeswaran, S; Manikandan, M
Abstract: To run the electric vehicle, battery system is used. In battery system internal heat is generated due to various reason such as close arrangement of cells, periodic recharge and discharge of batteries. This heat can cause reduction of driving range, System safety, Life time of battery and Efficiency. To eliminate the heat by introduction of Battery thermal management system. In Battery thermal management system various cooling arrangement configurations (1s, 2s, Parallel & Parallel with smooth tubes) are done to maintain the optimum temperature level of battery. This work is done by a Computational fluid analysis to characterize the temperature distribution of the battery under various configuration using Ethylene glycol and also Nano particles and Phase change material are introduced in the Lithium ion battery system Inlet velocity of fluid is given as 0.1m/s and the temperature is 300K. Heat generated by the cell is 4 watts per cell and the heat flux is 1.66*e^5 w/m^2[5].